2014
DOI: 10.1002/mrd.22328
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome analysis identifies regulated transcripts and pathways activated during oogenesis and early embryogenesis in atlantic cod

Abstract: The molecular mechanisms underlying oogenesis and maternally controlled embryogenesis in fish are not fully understood, especially in marine species. Our aim was to study the egg and embryo transcriptome during oogenesis and early embryogenesis in Atlantic cod. Follicles from oogenesis stages (pre-, early-, and late-vitellogenic), ovulated eggs, and two embryonic stages (blastula, gastrula) were collected from broodstock fish and fertilized eggs. Gene expression profiles were measured in a 44 K oligo microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 88 publications
2
24
0
Order By: Relevance
“…In addition, we used (A)+enriched RNA, instead of total RNA and our qPCR assay is designed to amplify a fragment from the coding region of sea bass amh (the protease cleavage region to be more precise) while in the study by García-López et al [62] primers were designed in the 3' UTR. Moreover, our results are also in line with a recent study performed on Atlantic cod showing high amh levels in follicles from pre-, early-, and late-vitellogenic stages [63]. Surprisingly, sea bass amhr2 expression levels did not follow its ligand expression trends and remained virtually invariable throughout the reproductive cycle.…”
Section: Expression Patterns Of Sea Bass Amh and Amhr2supporting
confidence: 91%
“…In addition, we used (A)+enriched RNA, instead of total RNA and our qPCR assay is designed to amplify a fragment from the coding region of sea bass amh (the protease cleavage region to be more precise) while in the study by García-López et al [62] primers were designed in the 3' UTR. Moreover, our results are also in line with a recent study performed on Atlantic cod showing high amh levels in follicles from pre-, early-, and late-vitellogenic stages [63]. Surprisingly, sea bass amhr2 expression levels did not follow its ligand expression trends and remained virtually invariable throughout the reproductive cycle.…”
Section: Expression Patterns Of Sea Bass Amh and Amhr2supporting
confidence: 91%
“…In support for this, the CTα mRNA level in the liver of rat was high before birth and decreased after birth, maybe due to reduced activity in cell division (Sesca et al, 1996). A recent study reported gene expression levels of cod eggs in 6 stages (Kleppe et al, 2014), and by analyzing their raw data (accession number E-MTAB-2170, http://www.ebi.ac.uk/arrayexpress), we found that the expression of pyct1a (ENSGAUG00000007851) was generally higher in the egg stages compared to the larvae stages (Fig. 4).…”
Section: De Novo Synthesis Of Pcmentioning
confidence: 78%
“…A custom, Agilent 44 k oligo microarray (A-MEXP-2226, ArrayExpress, EMBL-EBI) described by Kleppe et al (2014) was used. This microarray design is partly based on the Atlantic cod gene set described in Star et al (2011) as well as EST sequences from various cod tissues/developmental stages.…”
Section: Microarray Design and Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…To get rid of more incorrect data points, the KEGG annotations shared between cod and salmon were filtered according to a previously published protocol for salmon (Wang et al, 2014) and all probes displaying more than three hits in the salmon transcriptome was filtered away. In the cod microarray similar filtering has previously been performed, therefore none multiple transcriptome mapping sites were found for cod (Kleppe et al, 2014). This analysis left us with a total of 3,262 KEGG annotations which could be compared between species.…”
Section: Molecular Reproduction and Developmentmentioning
confidence: 99%